2013
DOI: 10.1007/978-1-62703-748-8_6
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Approaches for MicroRNA Expression Analysis

Abstract: Profiling microRNA (miRNA) expression is of widespread interest due to their critical roles in diverse biological processes, including development, cell proliferation, differentiation, and apoptosis. Profiling can be achieved via three major methods: amplification-based (real-time quantitative PCR, qRT-PCR), hybridization-based (microarrays), and sequencing-based (next-generation sequencing (NGS)) technologies. The gold standard is qRT-PCR and serves as a platform for single reverse PCR amplification experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Quantitative real-time PCR was performed on the ABI Prism 7300 HT Sequence Detection system (Applied Biosystems, Forster City, CA) using Power SYBR Green PCR Master Mix (Applied Biosystems) and the expression of miRNA was measured through Stem-loop RT-PCR method (Dedeoglu 2014). The relative expression level of CpCPR5 was normalized to the internal control b-actin, and U6 small nuclear (U6) was used to normalize the expression level of miR-932.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…Quantitative real-time PCR was performed on the ABI Prism 7300 HT Sequence Detection system (Applied Biosystems, Forster City, CA) using Power SYBR Green PCR Master Mix (Applied Biosystems) and the expression of miRNA was measured through Stem-loop RT-PCR method (Dedeoglu 2014). The relative expression level of CpCPR5 was normalized to the internal control b-actin, and U6 small nuclear (U6) was used to normalize the expression level of miR-932.…”
Section: Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…The results demonstrated that there was a general consistency between qPCR and high-throughput sequencing, though there were some differences in the results of the two different technologies. Previous studies have indicated that RNA-seq is an accurate and powerful tool to identify new miRNAs and quantify miRNA expression [25,26]. On the other hand, the small size and heterogeneity of microRNAs present challenges for detection by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences of primer for CYP6AG11 were listed in Table 1. MiRNA quantification was calculated by the Bulge-loop™ miRNA qRT-PCR method (Dedeoglu 2014; Fulci et al 2007) and primer sets (one RT primer and a pair of qPCR primers) specific for miR-278-3p were designed and listed in Table 1. The relative expression level of CYP6AG11 was normalized to the internal control β-actin , and U6 small nuclear ( U6 ) was used to normalize the expression level of miR-278-3p.…”
Section: Methodsmentioning
confidence: 99%